Artificial Attraction: Linking Vessel Monitoring System and Habitat Data to Assess Commercial Exploitation on Artificial Structures in the Gulf of Mexico - Gardner, Christopher; Goethel, Daniel R.; Karnauskas, Mandy; Smith, Matthew W.; Perruso, Larry; Walter, John F. (Frontiers in Marine Science, 2022)
Marine artificial structures provide important ecosystem benefits, but the extent to which commercially valuable reef fish species and their associated fisheries utilize artificial structures is still undetermined. However, the increasing implementation of onboard Vessel Monitoring Systems (VMS) now enables precise identification of catch and effort locations that can be linked via satellite coordinates to seafloor habitat maps. To better understand the distribution of fishing effort across artificial and natural reef types in the Gulf of Mexico, we present the first attempt to link VMS data from commercial reef fish vessels with high resolution habitat maps for an iconic species, red snapper (Lutjanus campechanus). By allocating landings from VMS-linked individual fishing trips to habitat type (i.e., natural reef, artificial structure, or uncharacterized bottom) and overlaying these with previously developed red snapper biomass distributions, we are able to develop one of the first fine-scale spatial maps of exploitation across the entire Gulf of Mexico. Results indicated that nearly half (46%) of commercial red snapper landings were extracted from artificial structures. The degree of exploitation was highly heterogeneous with several localized hotspots on natural reefs along the continental shelf break and offshore areas of the Northeast Gulf of Mexico. Similarly, there were distinct regional differences in fishing patterns: a majority of the landings from the state of Florida (~91%) came from natural reefs, whereas ~75% of landings were from artificial structures from all other Gulf of Mexico states combined. These results indicate that the potential for localized depletion exists for red snapper. The exploitation maps developed here can directly aid fisheries managers by highlighting specific habitats and locations that should be carefully monitored as catch limits continue to increase.